Screening of sorghum genotypes/varieties against shoot fly (Atherigona soccata Rondani) - Kachhadiya, N M; Ghelani, Y H; Patoliya, B V; Ghelani , M K; Godhani, H S (Indian Journal of Plant Protection, 2025)
Field experiments were carried out on screening of sorghum genotypes/varieties against shoot fly (Atherigona soccata Rondani)   at Krishi Vigyan Kendra, Junagadh Agricultural University, Amreli, Gujarat during Kharif, 2022 and 2023. The results revealed that, among the different tested sorghum genotypes/ varieties, based on per cent dead hearts, none of the genotypes /varieties could be categorised as highly resistant (HR). The genotype IS 2205 (20.71%) showed the lowest dead heart per cent and was categorized in resistant category (R). The genotypes/varieties SR 3048, SR 3049, GJ 44, GNJ 1 and SR 3061 exhibiting 25.21 to 33.28 per cent dead hearts were categorized as moderately resistant(MR). The genotypes SR 3072 (34.60%), SR 3107 (34.98%), SR 3076 (38.02%), SR 3052 (39.11%) and SR 3084 (39.14%) were categorized as moderately susceptible group, whereas Swarna (57.60%) was included under highly susceptible group due to higher per cent dead hearts. More or less similar trend was observed in case of shoot fly oviposition. The genotypes/varieties SR 3048, SR 3049, GJ 44 and GNJ 1 were found best as they registered higher grain and fodder yield.